Anaerobic Faecalicatena spp. degrade sulfoquinovose via a bifurcated 6-deoxy-6-sulfofructose transketolase/transaldolase pathway to both C2- and C3-sulfonate intermediates - Borusak, Sabrina; Denger, Karin; Dorendorf, Till; Fournier, Corentin; Lerner, Harry; Mayans, Olga; Spiteller, Dieter; Schleheck, David (Frontiers in Microbiology, 2024)
Plant-produced sulfoquinovose (SQ, 6-deoxy-6-sulfoglucose) is one of the most abundant sulfur-containing compounds in nature and its bacterial degradation plays an important role in the biogeochemical sulfur and carbon cycles and in all habitats where SQ is produced and degraded, particularly in gut microbiomes. Here, we report the enrichment and characterization of a strictly anaerobic SQ-degrading bacterial consortium that produces the C2-sulfonate isethionate (ISE) as the major product but also the C3-sulfonate 2,3-dihydroxypropanesulfonate (DHPS), with concomitant production of acetate and hydrogen (H2). In the second step, the ISE was degraded completely to hydrogen sulfide (H2S) when an additional electron donor (external H2) was supplied to the consortium. Through growth experiments, analytical chemistry, genomics, proteomics, and transcriptomics, we found evidence for a combination of the 6-deoxy-6-sulfofructose (SF) transketolase (sulfo-TK) and SF transaldolase (sulfo-TAL) pathways in a SQ-degrading Faecalicatena-phylotype (family Lachnospiraceae) of the consortium, and for the ISE-desulfonating glycyl-radical enzyme pathway, as described for Bilophila wadsworthia, in an Anaerospora-phylotype (Sporomusaceae). Furthermore, using total proteomics, a new gene cluster for a bifurcated SQ pathway was also detected in Faecalicatena sp. DSM22707, which grew with SQ in pure culture, producing mainly ISE, but also 3-sulfolacate (SL) 3-sulfolacaldehyde (SLA), acetate, butyrate, succinate, and formate, but not H2. We then reproduced the growth of the consortium with SQ in a defined co-culture model consisting of Faecalicatena sp. DSM22707 and Bilophila wadsworthia 3.1.6. Our findings provide the first description of an additional sulfoglycolytic, bifurcated SQ pathway. Furthermore, we expand on the knowledge of sulfidogenic SQ degradation by strictly anaerobic co-cultures, comprising SQ-fermenting bacteria and cross-feeding of the sulfonate intermediate to H2S-producing organisms, a process in gut microbiomes that is relevant for human health and disease.